Uniformly attracting limit sets for the critically dissipative SQG equation. (13th January 2016) - Constantin, Peter; Zelati, Michele Coti; Vicol, Vlad
Abstract: We consider the global attractor of the critical surface quasi-geostrophic (SQG) semigroup S ( t ) on the scale-invariant space . It was shown in [015 ] that this attractor is finite dimensional, and that it attracts uniformly bounded sets in for any, leaving open the question of uniform attraction in . In this paper we prove the uniform attraction in, by combining ideas from the De Giorgi iteration and nonlinear maximum principles.